Association of rs2435357 and rs2506030 polymorphisms in RET with susceptibility to hirschsprung disease: A systematic review and meta-analysis - Mu, Jianhua; Zhang, Yuxi; Liao, Guoying; Li, Xinxin; Luo, Yinyan; Huang, Zhaorong; Luo, Caiyun; Wu, Kai (Frontiers in Pediatrics, 2022)
Background: There are numerous published studies on the association between RET polymorphisms and susceptibility to Hirschsprung disease (HSCR). However, some of the results are inconsistent and the studies were conducted with small sample sizes. Therefore, we performed a meta-analysis to clarify the relationship. Methods: Relevant data were retrieved from PubMed, Web of Science, Cochrane Library, EMBASE, CNKI, and Google Scholar according to PRISMA guidelines. Odds ratios (OR) were calculated to assess susceptibility to HSCR. Meanwhile, heterogeneity and publication bias were also calculated by R software package (version 4.2.1). The protocol was published in PROSPERO (CRD42022348940). Results: A total of 12 studies were included in the meta-analysis and comprised 12 studies on the RET polymorphism rs2435357 (1939 subjects and 3613 controls) and 7 studies on the RET polymorphism rs2506030 (1849 patients with HSCR and 3054 controls). The analysis revealed that rs2435357 [A vs. G: odds ratio (OR) = 3.842, 95% confidence interval (CI) 2.829–5.220; AA vs. GG: OR = 2.597, 95% CI 1.499–4.501; AA+AG vs. GG: OR=6.789, 95% CI 3.0711–14.9973; AA vs. AG+GG: OR = 8.156, 95%CI 5.429–12.253] and rs2506030 (A vs. G: OR = 0.519, 95% CI 0.469–0.573; AA vs. GG: OR = 0.543, 95% CI 0.474–0.623; AA+AG vs. GG: OR = 0.410, 95% CI 0.360–0.468; AA vs. AG+GG: OR = 0.361, 95%CI 0.292–0.447) were significantly associated with susceptibility to HSCR. Conclusions: The polymorphisms rs2435357 and rs2506030 in the RET may be related to susceptibility to HSCR, of which rs2435357 (T>C) is the causal locus and rs2506030 (A>G) is the protective locus.